2016
DOI: 10.1159/000445843
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Method to Measure Glomerular Filtration Rate by Iohexol Plasma Clearance in Conscious Rats

Abstract: Background/Aims: Glomerular filtration rate (GFR) is the best index for evaluating renal function. We aimed to develop a simplified iohexol plasma clearance procedure for GFR measurement in rats without urine collection, animal catheterization or anesthesia, with limited sampling and requiring blood instead of plasma, to further reduce the sample volume and improve animal welfare. Methods: After iohexol injection (129.4 mg), samples were drawn according to 2-compartment kinetics and analyzed by high performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Iohexol is an iodinated, non-ionic radiographic contrast agent that has been proposed as an alternative exogenous marker for GFR evaluation [77]. Recent studies in rats from Carrera et al [81] showed an easy iohexol clearance measurement method, which prevents urine sampling, anesthesia, and animal catheterization. This procedure is similar to the non-steady state inulin clearance method.…”
Section: Iohexol Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Iohexol is an iodinated, non-ionic radiographic contrast agent that has been proposed as an alternative exogenous marker for GFR evaluation [77]. Recent studies in rats from Carrera et al [81] showed an easy iohexol clearance measurement method, which prevents urine sampling, anesthesia, and animal catheterization. This procedure is similar to the non-steady state inulin clearance method.…”
Section: Iohexol Clearancementioning
confidence: 99%
“…Next, an iohexol bolus is injected to the animal and blood samples are drawn at fixed times after the administration for plasma clearance evaluation. Plasma iohexol concentrations are then measured by HPLC [81]. The tracer concentration decay is finally analyzed according to a two-compartment kinetic model.…”
Section: Iohexol Clearancementioning
confidence: 99%
“…Zhiqing et al [20] also measured serum cystatin C at 8 weeks after DJB, finding that it was elevated relative to values in sham-operated rats. To date, no studies have directly measured glomerular filtration rate using available methodologies including plasma clearance of iohexol and transcutaneous measurement of FITC-sinistrin clearance [27,28].…”
Section: Metabolic and Renal Biochemical Parametersmentioning
confidence: 99%
“…Transcutaneous measurement of GFR can detect the clearance rate of a fluorescent inulin-like substance which can be injected through a venous catheter or via tail vein to avoid catheterization thus allowing serial measurements (52, 53). In a study by Carrara et al, injection of non-radiolabeled ioxhexol into conscious restrained rats followed by four small blood draws from a tail vein was sufficient to calculate GFR (54). This procedure, which requires analysis of iohexol by HPLC, was validated for male and female rats under healthy conditions or following renal injury (54).…”
Section: Experimental Studies Linking Birth Weight and Renal Riskmentioning
confidence: 99%
“…In a study by Carrara et al, injection of non-radiolabeled ioxhexol into conscious restrained rats followed by four small blood draws from a tail vein was sufficient to calculate GFR (54). This procedure, which requires analysis of iohexol by HPLC, was validated for male and female rats under healthy conditions or following renal injury (54). MRI with measurement of clearance by a contrast agent can also be used for estimation of GFR (55).…”
Section: Experimental Studies Linking Birth Weight and Renal Riskmentioning
confidence: 99%